Mechanical acupuncture at HT7 attenuates alcohol self-administration in rats by modulating neuroinflammation and altering mPFC-habenula-VTA circuit activity - Seo, Su Yeon; Bang, Se Kyun; Kang, Suk Yun; Cho, Seong Jin; Choi, Kwang-Ho; Ryu, Yeonhee (Frontiers in Behavioral Neuroscience, 2024)
Introduction Alcohol use disorder is a chronic disorder with significant limitations in pharmacological treatments, necessitating the exploration of non-pharmacological interventions. Methods We used a model of alcohol self-administration (10% v/v) to analyze behavioral, neurochemical, and signaling mechanisms. Results Our findings demonstrate that stimulation of the HT7 acupuncture point significantly decreased the frequency of active lever presses in rats self-administering alcohol (p < 0.05). Alcohol self-administration increased microglial activity and sigma 1 receptor expression in the habenula (Hb), while HT7 stimulation mitigated these effects, decreasing microglial activity and sigma 1 receptor levels (p < 0.05). Additionally, alcohol self-administration reduced brain-derived neurotrophic factor (BDNF) expression in the medial prefrontal cortex (mPFC) and increased tyrosine hydroxylase (TH) levels in the ventral tegmental area (VTA) (p < 0.05). HT7 stimulation reversed these alterations by increasing BDNF expression in the mPFC and decreasing TH levels in the VTA (p < 0.05). Further investigation revealed that BDNF microinjection into the mPFC inhibited sigma 1 receptor activity in the Hb, while microglial inhibition in the Hb decreased TH expression in the VTA (p < 0.05). The administration of the microglial inhibitor MINO to the Hb also reduced alcohol self-administration (p < 0.05). Discussion These results suggest that HT7 stimulation regulates the mPFC-Hb-VTA circuit, leading to decreased alcohol-seeking behavior. Our study demonstrates that HT7 acupuncture can modulate the mPFC-Hb-VTA circuit, providing a potential non-pharmacological treatment for alcohol-seeking behavior by influencing microglial activity, sigma 1 receptor expression, and TH levels. These findings contribute to a deeper understanding of the neural mechanisms underlying acupuncture’s therapeutic effects on alcohol use disorder.